2005
DOI: 10.1038/nature03711
|View full text |Cite
|
Sign up to set email alerts
|

Serum retinol binding protein 4 contributes to insulin resistance in obesity and type 2 diabetes

Abstract: In obesity and type 2 diabetes, expression of the GLUT4 glucose transporter is decreased selectively in adipocytes. Adipose-specific Glut4 (also known as Slc2a4) knockout (adipose-Glut4(-/-)) mice show insulin resistance secondarily in muscle and liver. Here we show, using DNA arrays, that expression of retinol binding protein-4 (RBP4) is elevated in adipose tissue of adipose-Glut4(-/-) mice. We show that serum RBP4 levels are elevated in insulin-resistant mice and humans with obesity and type 2 diabetes. RBP4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

98
2,045
36
50

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,860 publications
(2,253 citation statements)
references
References 45 publications
98
2,045
36
50
Order By: Relevance
“…33). Indeed, in the present study not only plasma TNF␣ levels but also RBP4 plasma concentration as well as phosphorylation status of AKT in the liver, all being parameters indicating insulin resistance, [34][35][36] were markedly altered in mice chronically fed fructose. Again, a similar effect of fructose feeding was not found in TLR-4 mutant mice.…”
Section: Discussionsupporting
confidence: 46%
“…33). Indeed, in the present study not only plasma TNF␣ levels but also RBP4 plasma concentration as well as phosphorylation status of AKT in the liver, all being parameters indicating insulin resistance, [34][35][36] were markedly altered in mice chronically fed fructose. Again, a similar effect of fructose feeding was not found in TLR-4 mutant mice.…”
Section: Discussionsupporting
confidence: 46%
“…Furthermore, in vitro studies demonstrated that retinol-RBP4 complex, but not apo-RBP, binds to TTR (3). In tune with these results, fenretinide, a drug that competes with retinol for binding to RBP4, inhibits its interaction with TTR and increases its renal clearance (3,5). Interestingly, knockouts of either RBP4 or TTR are viable, suggesting the existence of efficient compensatory mechanisms for the transport of retinol and thyroid hormones (3,4).…”
Section: Role Of Rbp4 and Ttr In Vitamin A Metabolismmentioning
confidence: 88%
“…The expression of RBP4 mRNA and protein was demonstrated in several extrahepatic tissues including adipocytes (3,5). Moreover, in mice lacking lecithin:-retinol acyltransferase, large amount of retinyl esters remain in the adipose tissue that are mobilized during dietary retinoid insufficiency (4), implying an important role of adipose tissue in retinol storage and mobilization.…”
Section: Role Of Rbp4 and Ttr In Vitamin A Metabolismmentioning
confidence: 99%
See 2 more Smart Citations